REGULATING EXPRESSION AND EQUALITY IN COLLEGIATE ESPORTS - Burk, Dan; Rosenblatt, Betsy (AoIR Selected Papers of Internet Research, 2021)
Competitive professional computer gaming or “eSports” has grown rapidly over the past decade, and has extended into collegiate play, where educational institutions have begun sponsoring eSports teams, leagues, and events. However, the expansion of eSports has been accompanied by concerns regarding the online gaming culture from which eSports proceeds. Copious research establishes that women are routinely subjected to gender-based harassment in computer games and game-related activity. In the context of American collegiate eSports, this implicates the law of educational equality known as “Title IX.” Institutions subject to Title IX are required to maintain a learning environment in which educational opportunities are not impeded by sexual harassment, which will be required of eSports as it has long been required for physical sports. Yet, unlike sports played in physical space, computer games are necessarily mediated by software, which has consistently been held to constitute protected speech under the First Amendment to the United States Constitution. In this paper we examine the First Amendment constraints on the regulation of eSport computer games under Title IX. We argue that to the extent that choices among gaming content may be dictated by the constraints of Title IX, care must be exercised to accommodate both the statutory requirements of educational opportunity and the constitutional requirements for expressive freedom.